From farm scale to village scale trade-offs : cereal crop residues use in an agro-pastoral system of the Sudanian zone of Burkina Faso - Andrieu, Nadine (2015)
Traditionally, cereal crop harvest residues are communally grazed by the ruminant herds of villagers and transhumant pastoralists in the agro-pastoral systems which predominate in the savannah zone of West Africa. We analysed the impact of the private use of crop residues by individual farmers on crop and livestock productivity at three scales: the field, farm, and village. We collected data in the village of Koumbia, located in the Sudanian region of Burkina Faso. Three types of farmers were identified: resource-poor farmers, predominantly livestock farmers, and resource-rich farmers. The trade-offs between different uses and users of cereal crop residues at the three scales were analysed through field surveys and a simple model of biomass flows. We considered current communal use practices and two alternative scenarios of private cereal crop residue use: (i) for composting (fertility scenario) and (ii) as fodder (fodder scenario). Our analysis of current practices confirmed that farmers left around 80% of cereal crop residues on their fields. Soil fertility for cereal production therefore could be improved through crop residue management at the farm scale. We also found that communal grazing benefited farmers with high numbers of livestock. Maize grain production at the farm scale was improved in both of the simulated scenarios. Yet these scenarios had a negative impact on fodder self-sufficiency at the village scale, and on the N balance of the savannah-derived rangelands. The negative impact was greater in the fertility scenario than the fodder stock scenario. Increasing cereal productivity at the farm scale cannot be achieved without considering the trade-offs involved at the village scale. Changes in practices will require negotiations between the different types of farmers involved. Participatory innovation platforms with discussion support tools like the model presented in our study can facilitate such negotiations.